Power and International Relations: The Cooperative Dimensión - Miranda-Delgado, Rafael Gustavo (2023)
Power has been the engine of international relations and is the key concept for its study. The Realist and Neo-Realist schools have been the dominant ones in the discipline of International Relations and have understood the power in an exclusively conflictual way. Therefore, the aim of this article is to analyze the cooperative dimension of power conceptually and empirically. The article states that the contemporary Global Order is distinguished by being more plural in terms of agents and issues. Then, to understand this diversity, a broader concept of power is needed, which includes its cooperative dimension.